The Modern Confederacy in South Carolina: The Confederate Battle Flag, Confederate Memory and White Southern Identity from Centennial to Sesquicentennial - Holmes, Thomas (2019)
This thesis interrogates the intersection of historical memory, white Southern identity and socio-political change through the conflicts over the Confederate battle flag on the State House grounds in Columbia, South Carolina, from its raising in 1961 to its removal in 2015. By examining the rhetoric and actions of flag supporters through the lens of historical memory, the study aims to highlight changes and continuations in the memory of the Confederacy for Southern whites, what socio-political and sociocultural factors affected these changes, and seeks to answer whether or not Confederate memory can ever be solely concerned with heritage. Fundamentally, this thesis argues that Confederate memory throughout this period served a critical purpose as a coded signifier of white racial identity as the concept of white racial identity became less obvious and often more contested as a hegemonic power and a distinctive cultural trait. This meant that Confederate memory adapted and changed with regard to the particular historical moment in order for it to be evoked by whites with the seeming air of historical authenticity. It is in this way that the Confederate flag issue was consistently enmeshed within broader socio-political discourses that, at their cores, pertained to the place of white Southern identity and to the often illusory threats to traditionalist white hegemony in a changing American South.